Performance of Sub-District Health Promoting Hospital: A Case study of Health Region 8 in Northeastern of Thailand - Kampaengsirichai, Jintana; Kunurat, Prasit; Erviana, Rima (International Journal of Psychosocial Rehabilitation, 2020)
— People’s wellbeing has played an important role in developing and increasing the competitiveness of the country. The government’s obligation is to get the public services to meet people’s health demands and give them valuable and quality performances. There are many factors affecting the achievement of the performance in health services. If the practical ways of dealing with those factors are in place, the achievement of performance can be greatly increased. The objective of this study was to investigate the factors affecting the achievement of the quality and valuable performances of Sub-District Health Promoting Hospitals in Health Region 8. This was a mixed-method research and the samples were the people who undertook services at sub-district health promoting hospitals. With the purposive sampling method, the sample group of this study were 315 people. The results showed that seven factors affecting the achievement of the quality and valuable in sub-district health promoting hospitals were Behavior, Service Quality Awareness, Social Psychology, Economy Society, Management, Medicine Technology and Operating Workload. These seven factors could predict the achievement of the valuable and quality performances towards the communities, which was statistically significant at p-value<0.05.They also explained factors affecting the achievement of the quality and valuable performances of the sub-district health promoting hospitals at 88.4 percent (R2 = 0.844).The relationship between service factors and the performance achievement was positive at high level. The findings showed that all the factors have affected the achievement of the quality and valuable performances and they can be applied to improve the performance achievement of other sub-district health promoting hospitals.